Generic drugs, a need to the public: USA and India – Government plans to reduce the price of abbreviated new drug application and list of generic drugs approved in year 2018. (September 2019) - Martin, Russell; Bahmani, Kavita
Health is the prime component for every person, and in the world, there are different traditions that have their own approaches to treat and cure illness. The dosage form of the drug may appear different but medically, however, a generic medicament has the same mechanism in the body as that of the costlier brand-name drugs. They acquire the equal active ingredient an have the identical quality asd must pass the same satisfactory standards with respect to manufacturing and packaging of medicaments. The generic medicinal drug beneath the regulation of U.S. Food and Drug Administration must have the equal quality and performance as that of the brand-name drugs. The Food and Drug Administration states: 'Generics have the identical quality as brand identify drugs'. When a generic drug product is approved, it has met rigorous standards established via the Food and Drug Administration with respect to identity, strength, quality, purity and potency. India started Jan Aushadhi scheme to make quality medicines handy to the shoppers at affordable prices. Given the socio-economic conditions and the level of ignorance and illiteracy with vast disparities of income in the country, the advantage of the scheme can be taken by the consumers or should reach the consumers particularly the poor and the needy, only when a proper multimedia publicity programmed is mounted to educate the consumers of all strata of society. India is still a developing country where quality and inexpensive remedy are still major issues.